Impact of medium power inverter-based residential harmonic loads and PFCs on low voltage lines - Au M.T.; Navamany J.S.; Yeoh E.C. (2023)
Combination of a large amount of harmonic currents produced by nonlinear/power electronic loads and capacitance in the network usually results in harmonic resonance which is detrimental to the performance of the distribution systems. Over the last few years, there has been a very significant increased in the usage of power electronic loads such as the inverter air-conditioners, inverters refrigerators, compact fluorescent lamps, etc. in residential households and small/medium commercial premises. At the same time, there is also a growing concern of meeting the required reactive power necessary for voltage regulation and minimize technical losses of the distribution network. This paper presents results of harmonic measurements of new types of individual harmonic loads such as the inverter control air conditioner and inverter refrigerators which contribute more than 50% of total energy used in residential households and analyze their impact on harmonic resonance in the presence of small power factor correction (pfc) capacitors installed extensively at low voltage (LV) service lines. Results of the analysis indicate that a continuous growth in the numbers of inverter control loads in residential households is likely to cause harmonic resonance, and increased in total harmonic voltage distortion (THDV) at point of common coupling (PCC). 2010 IEEE.